Optimizing management of treatment-naïve and treatment-experienced HIV+ patients: the role of maraviroc - Eva Poveda (Dove Medical Press, 2010)
Eva Poveda, Vincent SorianoDepartment of Infectious Diseases, Hospital Carlos III, Madrid, SpainAbstract: Maraviroc is the first CCR5 antagonist approved for the treatment of HIV-1 infection. It specifically inhibits the replication of R5 viruses by blocking viral entry. HIV-1 tropism can be estimated accurately and predict viral response to maraviroc. Genotypic tools are increasingly replacing phenotypic assays in most places. The favorable pharmacokinetic properties and the good safety profile of maraviroc may support an earlier use of the drug in HIV-1 infection, as well as favor its consideration as part of switch strategies in patients under suppressive antiretroviral regimens containing less-well-tolerated drugs. Moreover, a particular immune benefit of maraviroc might encourage its use as part of intensification strategies in HIV-infected patients with impaired CD4 gains despite prolonged suppression of HIV replication with antiretroviral therapy. However, the long-term consequences of using maraviroc must be carefully checked, given its particular mechanism of action, blocking a physiologic cell receptor.Keywords: maraviroc, tropism, HIV, antiretroviral therapy, treatment strategies